2009
DOI: 10.3844/ajidsp.2009.170.179
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Struvite Crystals in the Presence of Herbal Extract Boerhaavia diffusa Linn

Abstract: Problem statement: The formation of a urinary stone, known as nephrolithiasis, urolithiasis, renal calculi or kidney stone is a serious, debilitating problem in all societies throughout the world. Struvite or Ammonium Magnesium Phosphate Hexahydrate (AMPH) is one of the components of urinary stone (calculi). Struvite stones are commonly found in women. Struvites form in humans as a result of urinary tract infection with ureolithic urea splitting micro organisms. These stones can grow rapidly forming "staghorn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The results of the experiments further prove the citrate inhibition theory [50]. Previously, the detailed experimental data and outcomes of the growth inhibition studies of struvite crystals using different herbal extracts are very well discussed by Chauhan et al [47][48][49]. These experiments depicted that the growth rates were comparatively lower for the each of the herbal extracts in comparison to the control case.…”
Section: Mechanical Parametersupporting
confidence: 71%
See 2 more Smart Citations
“…The results of the experiments further prove the citrate inhibition theory [50]. Previously, the detailed experimental data and outcomes of the growth inhibition studies of struvite crystals using different herbal extracts are very well discussed by Chauhan et al [47][48][49]. These experiments depicted that the growth rates were comparatively lower for the each of the herbal extracts in comparison to the control case.…”
Section: Mechanical Parametersupporting
confidence: 71%
“…The gel acts as a growth medium and provides a simplified model for the complex process of urinary calculi growth. Recently, Chauhan and Joshi [46] have reported the growth inhibition studies of struvite by the juice of Citrus medica Linn as well as the herbal extracts of Commiphora wightii [47], Boerhaavia diffusa Linn [48] and Rotula aquatica Lour [49]. The medicinal values of the herbal extracts, constituent elements, experimental techniques and results were elaborately reported elsewhere [47][48][49].…”
Section: Growth Inhibition Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Struvite, accounts for 10-20 % of all renal calculi [2], and is one the major component of urinary stones. These stones can grow rapidly forming "staghorn-calculi", which is a more painful urological disorder [3] threatening human life particularly the women. Priestly and Dunn [4] reported that these stones have a significant chance of causing death in affected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lot of survey work for study of antilithic medicinal plants has been done by different researchers. These include studies on medicinal plants of Muzaffaranagar district (Chauhan et al, 2009) and Aravali regions of Rajasthan (Sharma et al, 2011) that are used in the treatment of urinary tract and kidney stone; studies on urinary diseases and ethnobotany among pastoral nomads in the Middle East (Rabia, 2005) and on herbal folk medicines used for urinary complaints in tribal pockets of Northeast Gujarat (Punjani, 2010).…”
mentioning
confidence: 98%